The Relationships Among Transverse Sinus Stenosis Measured by CT Venography, Venous Trans-stenotic Pressure Gradient and Intracranial Pressure in Patients With Unilateral Venous Pulsatile Tinnitus - Qiu, Xiaoyu; Zhao, Pengfei; Li, Xiaoshuai; Ding, Heyu; Lv, Han; Zeng, Rong; Wang, Guopeng; Jin, Long; Yang, Zhenghan; Gong, Shusheng; Wang, Zhenchang (Frontiers in Neuroscience, 2021)
Objectives: To assess a non-invasive means of predicting a venous trans-stenotic pressure gradient (TPG) and intracranial pressure (ICP) as opposed to invasive examinations in unilateral venous pulsatile tinnitus (PT) patients. Methods: Thirty patients with unilateral venous PT who presented symptomatic-sided transverse sinus stenosis (TSS) on computed tomography venography (CTV), ipsilateral TPG measured by digital subtraction angiography and cerebrospinal fluid pressure measured by lumbar puncture were included. The ratio of TSS was calculated by dividing the cross-sectional areas of the maximal stenosed transverse sinus by that of the adjacent normal transverse sinus on CTV. The correlations among and predictive values of TSS, TPG and ICP were analysed. Results: In patients with unilateral venous PT, the symptomatic-sided and average bilateral TSS values were 78±11% and 77±9%; ICP, 230.50±55.75 mmH2O; and the TPG, 9.51±5.76 mmHg. The symptomatic-sided TSS was linearly and positively correlated with TPG (R2=0.400), and the symptomatic-sided and bilateral average TSS both showed weak correlations with ICP (R2=0.288, R'2=0.156). When the degree of TSS increased by 10%, the TPG and ICP increased by approximately 3.3 mmHg and 25.8 mmH2O, respectively. The ROC curve showed the optimal threshold of ipsilateral TSS for a positive TPG was 0.75, while TSS had no significant predictive value for ICP (p>0.05). TPG and ICP also exhibited a linear positive correlation (R2=0.552). When ICP increased by 10 mmH2O, the TPG increased by approximately 0.77 mmHg, and the optimal threshold of ICP for a positive TPG was 227.5. Conclusion: TSS, TPG and ICP are interrelated. TSS measured by CTV can predict TPG in patients with unilateral venous PT.